I’ll read in English if...: A glimpse into the nature of tertiary ESL reading motivation - Murad Sani, Azlina; Tengku Ariffin, Tengku Faekah; Shaik Abdullah, Sarimah (Elsevier Ltd., 2014)
Reading is a process that involves effort and choice, hence the significance of motivation. In Malaysian public universities, students usually function in an academic domain where two literacies, English and Bahasa Malaysia, exist side by side, often within the same classroom.This rather unique context adds a new dimension to research on the multifaceted nature of reading motivation.The main objective of this paper is to describe various aspects of motivation for reading in English among undergraduate Malaysian ESL readers, along the constructs of extrinsic and intrinsic motivation, and in relation to gender and language proficiency.319 students responded to an adapted version of the Motivation for Reading Questionnaire (MRQ).Although motivation for reading in English was only at moderate levels, results showed a significantly higher level of extrinsic motivation, compared with intrinsic motivation.There was a preference for English reading for reasons related to tests, compliance and recognition.These findings were consistent across proficiency groups.However, females tended to have a higher level of motivation, especially in reading for test purposes.Findings suggest a performance orientation to reading, with external rewards and a competition to score good marks playing a bigger role than personal or social reasons in reading decisions.